Utilization of artificial circular RNAs as miRNA sponges and anti-PD-1 scFv expression platforms to suppress hepatocellular carcinoma progression - Lai, Yongping; Wang, Fei; Cai, Guang; Li, Yingying; Weng, Jiaxin; Cai, Feifan; Cai, Leijie; Cheng, Niangmei; Zhao, Bixing; Zeng, Yongyi (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is characterized by a complex interplay of genetic and epigenetic alterations that contribute to its aggressive nature and resistance to conventional therapies. The recent advent of immune checkpoint inhibitors has shown promise in enhancing the immune system's ability to target cancer cells. However, the efficacy of these therapies is often hindered by the tumor's immunosuppressive microenvironment. Circular RNAs (circRNAs), a class of non-coding RNAs, have emerged as promising candidates for the development of novel therapeutics due to their unique properties, including resistance to degradation and the ability to act as miRNA sponges.MethodsIn this study, we engineered artificial circRNAs to target oncogenic miRNAs and to express anti-PD-1 scFv antibodies, aiming to simultaneously disrupt oncogenic pathways and enhance the immune response against HCC.ResultsOur results demonstrate that the engineered circRNAs effectively sponge miR-25, leading to subsequent inhibition of HCC cell proliferation and angiogenesis. Moreover, the expression of anti-PD-1 scFv antibodies from the circRNAs significantly enhanced the cytotoxic T-cell response against HCC cells. In vivo studies revealed a significant reduction in tumor volume and prolonged survival in mice treated with the engineered circRNAs compared to controls.ConclusionsOur findings highlight the potential of artificial circRNAs as a novel therapeutic strategy for HCC. By harnessing their ability to act as miRNA sponges and to express immunomodulatory proteins, these engineered circRNAs offer a promising approach to overcome the challenges associated with HCC therapy.